Problems of preservation and accessibility of cartographic publications in the National Libraries of Russia - Kildushevskaya, Ludmilla (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
The preservation of cartographic publications are considered in the context of the National Program of Preservation of the Library Collections of the Russian Federation approved by the government of the Russian Federation in 2000. This Program is the first goal_oriented national library programme in the history of the country. The Program is planned for ten years and includes a number of subprogrammes: 1. Collection conservation. 2. Creation of the insurance stock of library documents and information preservation. 3. Book Monuments of the Russian Federation. 4. Library collection safety. 5. Collection preservation through specifying usage conditions. 6. Registration of library stocks. 7. Personnel ensuring the collection preservation processes. It is impossible to describe in one report all the ranges of work reflected in this extensive programme. Therefore, I will dwell on the special measures carried out by the divisions of cartography within the first three subprogrammes and the fifth one.